Research Information Management System and Financial Performance: Case of National Commission for Science Technology and Innovation, Kenya - Kuyan, Pauline Kipiku (Daystar University, School of Business and Economics, 2024)
Financial performance is crucial for organizations like the National Commission for Science Technology and InnovationNACOSTI) in Kenya, which encounters challenges such as lack of transparency in reporting, inefficient fund allocation, and difficulties in tracking project expenditures. These issues can lead to resource mismanagement and reduced accountability, ultimately hindering the organization's ability to fulfil its mandate. The implementation of a Research Information Management System (RIMS) at NACOSTI was meant to revolutionize the application and processing of research permits ultimately improving financial performance, informed by increased number of research permits granted. The study aimed to establish the roles of RIMS in research permit application; evaluate the financial performance of NACOSTI after RIMS; and examine the influence of RIMS on financial performance at NACOSTI. The study was guided by the Resource-based theory, System theory, Stewardship theory, and the Technology Acceptance Model (TAM). The study employed a descriptive-correlations research design. The target population was sampled through stratified random sampling, which led to 55 responses in total. Data was collected from the study participants at NACOSTI using a digitized questionnaire, digitized using Kobotoolbox.org and administered using Kobo-collect, a mobile application. The financial records of NACOSTI regarding research permit application and processing were used as secondary data. The study used SPSS Version 29, and data analysis results were presented using tables. The researcher proved reliability by using questionnaires that were administered during the pretest. Descriptive statistics in form of means and standard deviations were used to illustrate the results while correlation analysis and multiple linear regression were used in the study to model and examine the relationship between each independent variable and the dependent variable. The results showed that the RIMS system was able to organize research data in a structured and systematic way (93%), provided tools for data categorization and labelling (87), ensured security of the data and integrity while storing or retrieving (81%), provided departmental customizable options (86%) and ensuring data traceability through version control (81). Additionally, the system provided comprehensive data analytics and reporting functionalities that provided insights and trends that aided in decision making (72%). Finally, the system provided data security and preservation functionalities through backups and archiving while enhancing compliance with data protection regulations and standards (68%). The study reported increase in revenue from permits since the adoption of RIMS, increased efficiency in the application and processing of research permits and reduced processing and administrative costs. The analysis of secondary data reported 38,840,000 KES increase in revenue, four years since the adoption of the system.The study also reported a strong positive statistically significant correlation between financial performance and each of the roles of the system and the regression coefficients indicted an improvement in financial performance because of the system’s roles. The organization culture at NACOSTI supported investments in technology and innovation which catalysed the impact of RIMS to the financial performance of the organization. The study recommended the adoption of technologies and innovations by government organizations to improve service delivery to the citizenry while improving efficiency and fostering transparency and accountability.
Master of Business Administration in Finance
Keywords: Financial performance; National Commission for Science Technology and Innovation